The Effect Of The Student Facilitator And Explaining Method On Learning Outcomes In Terms Of Learning Styles In Terms Of Student Learning Styles - Sari, Mayang Bintan; Asrul; Maysarah, Siti (Yana Research, 2022)
This study aims to determine the effect of the student facilitator and explaining method on student learning outcomes with visual and auditory learning styles. This type of research is quantitative research using completely randomized design research. The subjects in this study were students of class XI MA Al-Falah. Based on the results of data analysis conducted, the researchers found that the learning outcomes of students with visual and auditory learning styles have increased. The results showed that there was a significant difference between before being given treatment and after being given treatment on student learning outcomes. Hypothesis testing with t-test at a significance level of 5%. The t-test analysis conducted on the average final test on student learning outcomes with visual and auditory learning styles showed that the value of tcount > ttable was 4.55 > 2.145, so H0 was rejected and Ha was accepted. So that the alternative hypothesis Ha stated